PERANCANGAN DASHBOARD PERFOMA SALES DI CV MIRKO SEJAHTERA ABADI - Jeffrey Triguna; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Dashboard is design for CV Mirko Sejahtera Abadi aims to improve the sales performance of CV Mirko Sejahtera Abadi. Making the dashboard can make CV Mirko Sejahtera Abadi easier to know their sales every month and also, they sales performance every month. The design of this dashboard uses the Waterfall model System Development Life Cycle (SDLC) development methodology. The database used in this application is MySQL. The programming languages used are HTML and PHP.